Pengaruh Penggunaan Alat Peraga Gamatek (Galacang Matematika) Terhadap Hasil Belajar Matematika Pada Murid Kelas IV SDN 74 Terasa Kabupaten Sinjai - Andi Husniati; Andi Ardillah Wahyudi; A.Nur Indah Purnamasari (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to determine the effect of using Gamatek teaching aids (Mathematics tutorials) on mathematics learning outcomes in class IV students at SD Negeri 74 Terasa, Sinjai Regency. This research is a type of Pre-Experimental research with a One Group Pre-test Post-test Design. This research involved 11 fourth grade students at SD Negeri 74 Terasa, Sinjai Regency. The data collection techniques are tests and observations. The data analysis technique in this research is descriptive statistics and inferential statistics. The research results show that 1) The student learning outcomes before using Gamatek teaching aids were 90.90% of students were incomplete and classified as needing guidance and did not meet the classical completeness criteria, namely ≥ 75%, 2) Student learning results after using Gamatek teaching aids showed 90.90% of students completed. Thus, student learning outcomes after using Gamatek teaching aids are classified as very good and have met the classical completeness criteria, namely ≥75%, 3) The student's average normalized gain of 0.65 is in the medium classification. Thus, it can be concluded that learning mathematics on KPK and FPB material using Gamatek (Mathematics Galacang) teaching aids is said to have an effect on improving the learning outcomes of class IV students at SD Negeri 74 Terasa, Sinjai Regency.